Reversing NK cell exhaustion: a novel strategy combining immune checkpoint blockade with drug sensitivity enhancement in the treatment of hepatocellular carcinoma - Huang, Yuxiang; Liao, Hengjian; Luo, Jiefu; Wei, Huaning; Li, Anling; Lu, Yujie; Xiang, Bangde (Frontiers in Oncology, 2025)
Hepatocellular carcinoma (HCC) is one of the most common lethal cancers worldwide. Natural killer cells (NK cells) play a key role in liver immunosurveillance, but in the tumor microenvironment, NK cells are readily depleted, as evidenced by down-regulation of activating receptors, reduced cytokine secretion, and attenuated killing function. The up-regulation of inhibitory receptors, such as PD-1, TIM-3, and LAG-3, further exacerbates the depletion of NK cells. Combined blockade strategies targeting these immunosuppressive mechanisms, such as the combination of PD-1 inhibitors with other inhibitory pathways (eg. TIM-3 and LAG-3), have shown potential to reverse NK cell exhaustion in preclinical studies. This article explores the promise of these innovative strategies in HCC immunotherapy, providing new therapeutic directions for optimizing NK cell function and improving drug sensitivity.